Photodynamic therapy following fractional CO2 laser for treatment of primary vulvar Paget's disease: does it really work?. (3rd October 2021) - Ferrara, Francesca; Bardazzi, Federico; Messori, Stefano; Abbenante, Diego; Barisani, Alessia; Vaccari, Sabina
Abstract: Introduction: Extra-mammary Paget's disease is a rare form of intraepithelial adenocarcinoma with a variable pattern of invasion. Vulvar Paget's disease represents 1% of all vulvar cancers. Standard treatment is surgical excision, however, the recurrence rate is high and surgery leads to anatomical, functional and sexual morbidity. Some studies suggest the efficacy of photodynamic therapy following CO2 Laser irradiation as treatment for this disease. Methods: In the present study, ten patients with vulvar Paget's disease underwent fractional carbon dioxide (CO2 ) laser abrasion, followed by 3 h of occlusive application of aminolaevulinic acid (ALA) and then 100 J/cm2 irradiation with a 630-nm lamp. This combination treatment regime was repeated every 2 weeks for a total of 5 times. Results: At the end of the 12-month follow-up period, only two patients maintained a complete remission of the disease and recurrence was observed in all patients who had originally shown a partial remission. Conclusions: According to our experience, Photodynamic Therapy-ALA following fractional CO2 Laser does not seem to be an effective treatment for vulvar EMPD in the long term.